2019
DOI: 10.1002/smll.201904022
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Materials–Based Electrochemical Biosensors from Enzymatic to Nonenzymatic

Abstract: Mesoporous materials have drawn more and more attention in the field of biosensors due to their high surface areas, large pore volumes, tunable pore sizes, as well as abundant frameworks. In this review, the progress on mesoporous materials–based biosensors from enzymatic to nonenzymatic are highlighted. First, recent advances on the application of mesoporous materials as supports to stabilize enzymes in enzymatic biosensing technology are summarized. Special emphasis is placed on the effect of pore size, pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 125 publications
0
45
0
Order By: Relevance
“…[8] Especially, mesoporous materials have aroused increasing attention owing to their advantages of high specific surface area, high porosity and substantial mesoporous channels. [9] Nowadays, many mesoporous materials such as mesoporous SiO 2 , TiO 2 , have been used as catalysts or catalyst supports, [10] but researches on mesoporous phosphides have seldom been reported. As far as we know, most of the reported mesoporous phosphides were prepared by decomposition of a metal hydroxide or oxyhydroxide precursor and subsequent phosphidation reaction, which means the so-called mesopores were formed by stacking of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Especially, mesoporous materials have aroused increasing attention owing to their advantages of high specific surface area, high porosity and substantial mesoporous channels. [9] Nowadays, many mesoporous materials such as mesoporous SiO 2 , TiO 2 , have been used as catalysts or catalyst supports, [10] but researches on mesoporous phosphides have seldom been reported. As far as we know, most of the reported mesoporous phosphides were prepared by decomposition of a metal hydroxide or oxyhydroxide precursor and subsequent phosphidation reaction, which means the so-called mesopores were formed by stacking of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…A nanoporous material with uniform mesoporosity has been applied to synthesize functional nanobiomaterials in various fields, such as separation, sensors, catalysis, biofuel cells, energy conversion, drugs, and others. The strategy for using the nanoporous material is roughly classified to the confinement of biomacromolecules inside the mesosized cavity [7][8][9][10][11][12][13][14][15][16] and the hierarchical immobilization of biomacromolecules at the external material surface. [17][18][19][20][21] The confinement of a protein has usually been utilized to improve the stability and activity of a biomolecule.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] The confinement of a protein has usually been utilized to improve the stability and activity of a biomolecule. [7][8][9][10][11][12][13][14][15][16] The peptides, oligonucleotides, and proteins at the external material surface have been used for improving the biocompatibility of the nanoporous material, efficient and selective binding of the nanoporous material, and the regulation of mass transfer across the pore entrance. [7][8][9][10][11][12][13][14][15][16] In any application, nanoporous materials with mesoporosity (pore size of 2 to tens of nm) have been used, because the dimensions of biomacromolecules, such as peptides, oligonucleotides, and proteins, are more than a few nm.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, enzyme based biosensors suffer denaturation of the enzyme and different efforts have been done to improve their stability. Inorganic compounds that mimic the electrocatalytic activity of enzymes have been extensively studied in recent years [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of PB as a recognition element for H 2 O 2 detection is extensive [ 14 , 15 , 16 ]. Furthermore, in order to increase the sensitivity and the rapid response of electrochemical sensors, nanomaterials and nanostructured systems are used to modify the electrode surface, since it has been reported that nanomaterials promote electron transfer more efficiently between the electrodes [ 6 , 7 , 8 , 11 , 17 , 18 , 19 ]. On the other hand, carbon nanotubes possess interesting chemical and physical properties, which are useful in order to modify electrochemical sensors, therefore, the combination of PB, carbon nanotubes (CNTs), and metals have received special attention.…”
Section: Introductionmentioning
confidence: 99%